The social construction of disappointment in the monodrama Fi Intizār Rādī: Analysis of the phenomenon of the defeated generation through the perspective of Peter L. Berger - Jasmiko Jasmiko; Aina Mardiyah Caniago; Ali Reza Fadilah (Privietlab, 2026)
This article aims to analyze the monodrama Fi Intizār Rādī by Bassam Hassan using the framework of the Social Construction of Reality Theory by Peter L. Berger and Thomas Luckmann. This research dissects how the social, political, and economic crises in post-Arab Spring Egypt have gone through three dialectical moments of social construction–Externalization, Objectivation, and Internalization–which ultimately shape Saber's identity as a member of the defeated generation. The results of the analysis indicate that Saber's narrative concerning bureaucratic corruption and the betrayal of the revolution is a reality that has been objectivized, mentally and physically imprisoning the individual. Saber internalizes this reality, which manifests as existential stasis, illness, and ultimately, death. Thus, Fi Intizār Rādī dramatically represents society’s failure to legitimate a just universe of meaning, compelling Saber to search for meaning in nothingness.